Analisis Penerapan Metode Single Index Model dan Constant Correlation Model dalam Optimalisasi Portofolio Saham Indeks LQ-45 di Bursa Efek Indonesia (BEI) Periode 2019-2021 - Yuningsih Wagafir; Yayu Isyana Pongoliu; Herlina Rasjid (Scimadly Publishing, 2022)
This study aims to determine the optimal stock portfolio using the single index model method and the constant correlation model method during the covid-19 pandemic. The data used is secondary data obtained from the company's stock price data on the Indonesia Stock Exchange. The sample in this study are companies that are included in the LQ-45 index during the 2019-2021 period. Data analysis in this study used the single index model method and the constant correlation model method in the Excel and SPSS programs. The results show 1) that stocks on the LQ-45 index that can form an optimal portfolio using the single index model method during the covid-19 pandemic are TBIG shares, MIKA shares, and MDKA shares. The portfolio return of the three stocks is 1.54%. Meanwhile, the portfolio risk value of the three stocks is 0.30%. 2) stocks on the LQ-45 index that can form an optimal portfolio using the constant correlation model method during the covid-19 pandemic are MDKA shares, TBIG shares and ANTM shares. The portfolio return of the three stocks is 1.99%. Meanwhile, the portfolio risk of the three stocks is 1.15%. There is no significant differences in return and risk in the single index model method and the constant correlation model method during the covid-19 pandemic.